2017
DOI: 10.4209/aaqr.2016.07.0312
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Amino-Functional Graphene/CNT Aerogel Adsorbent for Formaldehyde Removal from Indoor Air

Abstract: A flexible approach prepares amino-functional graphene aerogels with different additions of carbon nanotubes (CNTs) for use as an adsorbent to study the adsorption performance of formaldehyde in indoor air. Experimental results indicated that the decoration of amino groups offers a greater number of chemical adsorption sites, which mainly contributed to the improvement of the chemical adsorption capacity of graphene aerogels, and the breakthrough time increased from 0 to 390 min g -1 under 3.7 ppm of formaldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Ahmaruzzaman and Gupta 6 showed that the modification of rice husks could remove lignin and hemicellulose, reduce cellulose crystallinity, and increase the porosity or surface area. The SSA and pore volume results presented the same trend in our study, indicating that the microstructure and pore properties of rice straw benefited from the modification 27 . The Tiron-extractable Si contents were 41.2, 182.3, 168.5, and 20.1 g·kg −1 in Sp, Sa, Sb, and Ms, respectively, according to the analytical method of Guntzer et al .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Ahmaruzzaman and Gupta 6 showed that the modification of rice husks could remove lignin and hemicellulose, reduce cellulose crystallinity, and increase the porosity or surface area. The SSA and pore volume results presented the same trend in our study, indicating that the microstructure and pore properties of rice straw benefited from the modification 27 . The Tiron-extractable Si contents were 41.2, 182.3, 168.5, and 20.1 g·kg −1 in Sp, Sa, Sb, and Ms, respectively, according to the analytical method of Guntzer et al .…”
Section: Resultssupporting
confidence: 84%
“…The adsorption of Cd(II) onto the adsorbent with a larger SSA was more sensitive to the temperature than that with a smaller SSA. A higher SSA of an adsorbent indicated more adsorption sites, contact area and surface functional groups 27 . Therefore, the adsorbent with a higher SSA was more susceptible to temperature change and thus the thermal motion of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that can enhance the formaldehyde absorption is the surface properties of hBN. Hydrogen bonding between formaldehyde and hydroxyl or amine groups is very crucial in the absorption of formaldehyde 49 , 50 , while the formaldehyde molecules and hBN layers show both planar configuration, resulting in lower adsorption resistance 46 . Finally, formaldehyde has π-bonding between C and O atoms, while hBN also shows large 2D delocalized π-bonded structure.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, FA adsorption capacity of neat GA is less than expectations due to stacking of graphene nanosheets, while relevant modified studies are limitedly published in recent years. For instance, Jie Ma [16] et al manufactured composite GAs by direct additions of CNT into GO solution with 18 mg g -1 FA adsorption capacity. Lirui Wu [17] et al prepared ethylenediamine-modified graphene sponge with enhanced FA adsorption capacity of 22.8 mg g -1 , and amine groups of ethylenediamine was essential for improvement of FA removal.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, FA adsorption capacity of neat GA is less than expectations due to stacking of graphene nanosheets, while relevant modified studies are limitedly published in recent years. For instance, Jie Ma [ 16 ] et al. manufactured composite GAs by direct additions of CNT into GO solution with 18 mg g ‐1 FA adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%